Association between the consumption of antioxidant nutrients with lipid alterations and cardiometabolic risk in adolescents - Monteles NASCIMENTO, Larisse; Oliveira GOMES, Keila Rejane; Medeiros MASCARENHAS, Marcio Denis; Soares MIRANDA, Cassio Eduardo; Evangelista de ARAÚJO, Telma Maria; de Macedo Gonçalves FROTA, Karoline (Revista de Nutrição, 2023)
Objective This study aimed at validating the associations between the consumption of antioxidant nutrients as well as lipid alterations and cardiometabolic risks in adolescents. Methods This cross-sectional study included 327 adolescents aged 14-19 years. Sociodemographic and dietary information, anthropometric and blood pressure measurements, and biochemical data were obtained. Cardiometabolic risk was calculated by aggregating the risk factors, which were expressed as the sum of Z-scores. Poisson regression was performed to estimate the prevalence ratios. Results In boys, low intake of zinc was associated with elevated total cholesterol and triglyceride levels, whereas it was associated with low high-density lipoprotein cholesterol levels and high low-density lipoprotein cholesterol and total cholesterol levels in girls, thus indicating a cardiometabolic risk. Furthermore, low intake of copper was associated with high triglyceride levels and cardiometabolic risk in girls. The high prevalence ratios of high low-density lipoprotein cholesterol and total cholesterol levels and cardiometabolic risk were higher in those with low intake of vitamin A. Among girls, associations were also observed between lower intake of vitamin A and high triglyceride levels. Low intake of vitamin C among boys was associated with elevated high low-density lipoprotein cholesterol and triglyceride levels. Among girls, the intake of this vitamin was associated with lower low high-density lipoprotein cholesterol levels. In girls, low intake of vitamin E was associated with low low high-density lipoprotein cholesterol levels and high total cholesterol levels. Conclusion The associations between antioxidant micronutrients as well as lipid alterations and cardiometabolic risk emphasize the importance of encouraging the consumption of foods that are rich in these nutrients to modulate lipid alterations and cardiometabolic risk.